Desempenho produtivo e qualidade de ovos de poedeiras alimentadas com diferentes fontes de cálcio - Lima, Hiagos Felipe Firmino de (Universidade Federal Rural do Semi-Árido, 2016)
In animal production, where food represents about 70% of the cost of production, the supply of calcium to participate in large numbers in feed formulations, become the use of mineral origin organic important to maximize animal performance and minimize costs. Taking up the importance of integrity and eggshell strength in the conservation of its nutritional and microbiological property that mean the product quality and food safety, these features become essential for the approval of the egg by the consumer market. The objective was to evaluate different sources of calcium in diets on growth performance and eggs quality of laying hens light. The cages are equipped with linear feeder in galvanized sheet and drinker type nipple. The birds were housed in shed screen, in masonry, with clay tile roof equipped with 120 metal cages (0,20m x 0,40m x 0,40m) galvanized wire provided sideboard eggs arranged in four rows with corridor central. We used 120 birds of Bankiva line in the initial laying phase, starting the experiment when animals were in egg production and body weight even, the experimental period was 22-34 weeks old and the birds distributed in a completely randomized design with four treatments. Each treatment had 10 repetitions with 3 birds each unit experimental and consisted of four experimental diets with different sources of calcium: limestone, búzio shell flour (Anomalocardia brasiliana), oyster shell flour (Crassostrea brasiliana) and egg shell flour. Were evaluated: egg production rate, feed intake, feed conversion, absolute and relative weight of yolk, albumen and shell, height and width of the egg, specific gravity, yolk color, eggshell thickness, Haugh unit, albumen and yolk index. Had no significant effect (P> 0.05) between the treatments, for performance variables, egg production rate had a significant effect (P <0.05), its worst result egg shell flour. The egg shell flour was the only treatment showed significantly (P <0.05) for the weight, height and width of the egg, specific gravity, height and width albumen yolk, yolk absolute weight, albumen and shell, relative weight of the albumen and shell thickness, with worse results compared to the other treatments. Therefore, limestone, búzio shell flour and oyster shell flour, can be used as a source of calcium for laying rations
Productive performance and eggs quality of laying hens fed with different calcium sources
Keywords: Egg; Egg shell flour; whelk shell flour; Oyster shell flour; limestone; Ovo; Farinha de casca de ovo; Farinha de concha de búzio; Farinha de concha de ostra; Calcário calcítico; CIENCIAS AGRARIAS::MEDICINA VETERINARIA